Agenda Setting and Evidence in Maternal Health: Connecting Research and Policy in Timor-Leste - Wild, Kayli; Kelly, Paul; Barclay, Lesley; Martins, Nelson (Frontiers in Public Health, 2015)
The evidence-based policy (EBP) movement has received significant attention in the scientific literature, however, there is still very little empirical research to provide insight into how policy decisions are made and how evidence is used. The lack of research on this topic in low and middle-income countries is of particular note. We examine the maternity waiting home policy in Timor-Leste to understand the role of context, policy characteristics, individual actors and how evidence is used to influence the policy agenda. The research tracked the maternity waiting home policy from 2005 to 2009 and is based on in-depth interviews with 31 senior policy-makers, department managers, non-government organisation (NGO) representatives and United Nations (UN) advisors. It is also informed by direct observation, attendance at meetings and workshops and analysis of policy documents. The findings from this case study demonstrate the importance of political context, policy characteristics and the power of senior Ministry of Health officials rather than donors in setting the policy agenda. Maternity waiting homes were appealing because they were a visible, non-controversial and logical solution to the problem of accessing maternal health services. Evidence was used in a variety of ways, from supporting pre-determined agendas to informing new policy directions. In the pursuit of EBP, we conclude that the power of research to inform policy lies in its timeliness and relevance, and is facilitated by the connection between researchers and policy-makers.